Analysis of a newly developed locomotive engine employing sustainable fuel blends with hydrogen. (1st July 2022) - Seyam, Shaimaa; Dincer, Ibrahim; Agelin-Chaab, Martin
Highlights: Hybrid combined engine contains gas turbine, fuel cell, and on-board hydrogen production. Five alternative fuels are included in fueling system. The hybrid combined engine produces 7211 kW power double than of gas turbine engine. The thermal and exergy efficiencies can reach to 48% and 50%, respectively. The GHG emissions are dropped to more than 70% using alternative fuels. Abstract: Transportation emissions from fossil fuels and low efficiency engines significantly contribute to global warming. One way to mitigate this is to develop more efficient engines and use sustainable fuels. This paper presents a novel hybrid locomotive engine to replace the EMD 16-710G3 engine used for Canada's rail transportation. It consists of a gas turbine instead of an internal combustion engine, solid oxide fuel cell with steam reformer and water gas shift reactor, and thermoelectric generator and absorption refrigeration system for energy recovery, and onboard hydrogen production using aluminum electrolysis cell and proton exchange membrane fuel cell. The used fuels are methanol, hydrogen, methane, ethanol, and dimethyl ether rather than diesel fuel. This integrated system is investigated thermodynamically to evaluate the energy performance. The system performance is increased from 40% to 48% and 50% of energy and exergetic efficiencies, while the total power is increased from 3383 kW to 7211 kW using a methane and hydrogen blended fuel. Also, the engine has an efficiency above 60% using a dimethyl ether and hydrogen blend. Using alternative fuels helps reduce CO2 emissions by 50% for the methane and hydrogen blend and more than 70% for the other blends, such as ethanol and dimethyl ether blended with hydrogen. The proposed engine can potentially be applied to improve the overall system performance and reduce the environmental impact.